2013
DOI: 10.3389/fnhum.2013.00150
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the Role of the pre-SMA in Response Inhibition and Switching: A Combined Online and Offline TMS Approach

Abstract: The pre-supplementary motor area (pre-SMA) is considered to be a key node in the cognitive control of actions that require rapid updating, inhibition, or switching, as well as working memory. It is now recognized that the pre-SMA is part of a “cognitive control” network involving the inferior frontal gyrus (IFG) and subcortical regions, such as the striatum and subthalamic nucleus. However, two important questions remain to be addressed. First, it is not clear if the main role of the pre-SMA in cognitive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 56 publications
3
94
0
Order By: Relevance
“…Amongst the various processes by which the pre-SMA is considered to exert top-down control [34][35][36][37], our results suggest a predominant role in reactive motor inhibition, without a significant contribution to conflict resolution (see next section for interpretation). Previous imaging evidence shows activation of the pre-SMA during performance of the go no-go [38,39], or stop signal tasks [3][4][5]7,9,21].…”
Section: Motor Inhibitionmentioning
confidence: 63%
See 1 more Smart Citation
“…Amongst the various processes by which the pre-SMA is considered to exert top-down control [34][35][36][37], our results suggest a predominant role in reactive motor inhibition, without a significant contribution to conflict resolution (see next section for interpretation). Previous imaging evidence shows activation of the pre-SMA during performance of the go no-go [38,39], or stop signal tasks [3][4][5]7,9,21].…”
Section: Motor Inhibitionmentioning
confidence: 63%
“…In addition to inhibition, the pre-SMA has been implicated in several other cognitive control mechanisms, such as switching, updating or initiation of actions [8,[51][52][53][54]. It is not surprising that brain networks involved in inhibition, namely the pre-SMA and the STN, also operate during conflict resolution and switching, as shown previously [4,7], although other studies show greater anterior cingulate cortex (ACC) activity in conflict resolution [55,56].…”
Section: Conflict Resolutionmentioning
confidence: 88%
“…Human lesion and temporal lesion studies using TMS provide converging evidence for the critical role of the rIFG in response inhibition, with response inhibition impaired in patients with lesions to the rIFG Aron, Monsell, Sahakian, & Robbins, 2004;Obeso, Robles, Marron, & Redolar-Ripoll, 2013;Zandbelt, Bloemendaal, Hoogendam, Kahn, & Vink, 2013). Furthermore, using repetitive transcranial magnetic stimulation (rTMS) over rIFG but not left IFG has been shown to cause impairments in stopping but not going (Chambers et al, 2007), thus further supporting the rIFG's critical role in response inhibition.…”
Section: Neural Substrates Of Response Inhibitionmentioning
confidence: 99%
“…Outside the PFC, TMS Floden & Stuss, 2006;Obeso, Cho, et al, 2013;Obeso, Robles, et al, 2013) and tDCS (Hsu et al, 2011) over pre-SMA has also been shown to disrupt inhibitory performance, while neuroimaging studies have found successful inhibition to be associated with activity in the pre-SMA Swann et al, 2012), STN (Alegre et al, 2013;Isoda & Hikosaka, 2008;Li, Yan, Sinha, & Lee, 2008), striatum (Watanabe & Munoz, 2011;Zandbelt & Vink, 2010), and globus pallidus pars interna .…”
Section: Neural Substrates Of Response Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation